2021
DOI: 10.1111/iwj.13534
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment related skin reactions in healthcare professionals during COVID‐19

Abstract: Since the outbreak of COVID‐19 pandemic, clinicians have had to use personal protective equipment (PPE) for prolonged periods. This has been associated with detrimental effects, especially in relation to the skin health. The present study describes a comprehensive survey of healthcare workers (HCWs) to describe their experiences using PPE in managing COVID‐19 patients, with a particular focus on adverse skin reactions. A 24‐hour prevalence study and multi‐centre prospective survey were designed to capture the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 22 publications
3
86
1
4
Order By: Relevance
“…The flow diagram is presented in Online Appendix 3. We included 12 cross-sectional studies (Bharatendu et al., 2020; Çağlar et al., 2020 ; Hajjij et al., 2020 ; Heider et al., 2021 ; Jiang, Liu, et al., 2020 ; Jiang, Song, et al., 2020 ; Ong et al., 2020 ; Ramanan et al., 2020 ; Swaminathan et al., 2020 ; Tabah et al., 2020; Unoki et al., 2020; Xia et al., 2020 ), three case reports ( Chiriac et al., 2020 ; Dell’Era et al., 2020 ; Lam et al., 2020 ), three reviews ( Downie, 2020 ; Gefen & Ousey, 2020 ; Gross et al., 2021 ), including a systematic review, two observational studies ( Abiakam et al., 2021 ; Choudhury et al., 2020 ) including a study combined with a point prevalence study, a retrospective study ( He et al., 2020 ), two qualitative studies ( Begerow et al., 2020 ; Hoernke et al., 2021 ), and two letters without cases or data ( Goh et al., 2020 ; Wiwanitkit, 2020 ). Participants of seven studies were exclusively HCWs working in the ICUs; however, participants of the remaining studies included HCWs working in the ICU.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The flow diagram is presented in Online Appendix 3. We included 12 cross-sectional studies (Bharatendu et al., 2020; Çağlar et al., 2020 ; Hajjij et al., 2020 ; Heider et al., 2021 ; Jiang, Liu, et al., 2020 ; Jiang, Song, et al., 2020 ; Ong et al., 2020 ; Ramanan et al., 2020 ; Swaminathan et al., 2020 ; Tabah et al., 2020; Unoki et al., 2020; Xia et al., 2020 ), three case reports ( Chiriac et al., 2020 ; Dell’Era et al., 2020 ; Lam et al., 2020 ), three reviews ( Downie, 2020 ; Gefen & Ousey, 2020 ; Gross et al., 2021 ), including a systematic review, two observational studies ( Abiakam et al., 2021 ; Choudhury et al., 2020 ) including a study combined with a point prevalence study, a retrospective study ( He et al., 2020 ), two qualitative studies ( Begerow et al., 2020 ; Hoernke et al., 2021 ), and two letters without cases or data ( Goh et al., 2020 ; Wiwanitkit, 2020 ). Participants of seven studies were exclusively HCWs working in the ICUs; however, participants of the remaining studies included HCWs working in the ICU.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles investigated specific symptoms, such as PPE-related headaches (Bharatendu et al., 2020; Goh et al., 2020 ; Hajjij et al., 2020 ; Ong et al., 2020 ) and voice disorders ( Heider et al., 2021 ). Nine studies reported PPE-related skin injuries and manifestations ( Abiakam et al., 2021 ; Chiriac et al., 2020 ; Dell’Era et al., 2020 ; Downie, 2020 ; Gefen & Ousey, 2020 ; Jiang, Liu, et al., 2020 ; Jiang, Song, et al., 2020 ; Lam et al., 2020 ; Wiwanitkit, 2020 ). After conceptual classification, we concluded that the studies covered four key topics: PPE-related headaches, voice disorders, and skin injuries and/or manifestations, and miscellaneous AEs of PPE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Filtering facepiece respirator masks are designed to protect HCWs from infection whilst treating patients, as distinct from surgical masks which are intended to protect others from the wearer (9). Reported limitations of N95/FFP3 masks include interface pressure between the mask and face, thermal discomfort and skin tissue injury after long-term use, impairment to breathing, failure of the face-mask seal whilst talking and recurrent fit testing failure for certain face shapes, effectively removing ∼5% of the workforce (10)(11)(12)(13). The standard that defines FFR efficiency allows 5% inward leakage maximum, and 1% aerosol filter penetration by 0.02-2 µm (median 0.6 µm) particles (14).…”
Section: Introductionmentioning
confidence: 99%